Habitual Coffee Consumption Does Not Correlate with Blood Pressure, Inflammation and Endothelial Dysfunction but Partially Correlates with Oxidative Stress - Erizal Sugiono; Mansyur Arif; Anwar Santoso (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Coffee is the most widely consumed beverage in the world and has been known to have effects on cardiovascular system. Many researchers have examined the effects of coffee consumption on blood pressure (BP) and risk of cardiovascular disease (CVD), but their results were inconsistent and still remain a subject of controversy. Oxidative stress, inflammation, and endothelial dysfunction have been known as risk factors of hypertension and CVD. Those factors are also known to be affected by coffee consumption. The aim of this study was to examine the relationship between the effects of habitual coffee consumption on BP and to examine the role of oxidative stress (F2 isoprostane), inflammation (high sensitive C-reactive protein (hsCRP)) and endothelial dysfunction (asymmetric dimethylarginine (ADMA)).METHODS: This was a cross-sectional study in which 47 healthy, non-smoking men aged 30-60 years with varying coffee-drinking habits were enrolled. BP and blood/urine analysis of biomarkers were measured in the morning before activity. Coffee consumption was assessed using a questionnaire. The differences among variables were analyzed using ANOVA and the correlations between variables were analyzed using Kendall’s Tau correlation analysis.RESULTS: Habitual coffee consumption did not correlate with systolic/diastolic BP (r=-0.02; p=0.856 and r=0.15; p=0.230, respectively). Concentrations of ADMA and hsCRP were also not correlated with coffee consumption (r=0.03; p=0.764 and r=0.04; p=0.701, respectively). Coffee consumption only showed significant correlation with F2 isoprostane (r=0.34; p=0.004).CONCLUSION: BP was not affected by coffee consumption although coffee consumption has a significant correlation with F2 isoprostane. These findings suggest that correlation between coffee consumption and BP might be explained by other factors that were not included in this study.KEYWORDS: coffee, caffeine, cardiovascular disease, blood pressure, oxidative stress, inflammation, endothelial dysfunction